Can therapists and senior advisors predict improvement of PTSD severity, based on clinical intuition and liking of their patients? - Enning, Frank; Priebe, Kathlen; Steil, Regina; Görg, Nora Saskia; Müller-Engelmann, Meike; Schmahl, Christian; Kleindienst, Nikolaus (European journal of psychotraumatology, 2025)
Objective: Predicting symptom improvement in psychotherapy is a complex challenge. This study aims to extend traditional prediction methods by examining the potential roles of therapists’ and senior advisors’ clinical judgments and of their levels of liking of patients in predicting symptom improvement. Methods: Eighty women with PTSD related to childhood abuse treated with either cognitive processing therapy (CPT) or dialectical behaviour therapy for PTSD (DBT-PTSD) were included in the study. Four general linear models were used for predicting pre-to-post changes in the Clinician-Administered PTSD Scale (ΔCAPS) from (i-ii) the therapists’ and senior advisors’ intuitive predictions of symptom change, and (iii-iv) the therapists’ and senior advisors’ liking of their patient. These four ratings were assessed after the fourth therapy session. Results: Therapists’, but not clinical senior advisors’ intuitive predictions emerged as a strong and significant predictor of ΔCAPS (F1,73 = 11.37, p = .0012, partial η2 = 0.1348, and F3,69 = 1.04, p = .3799). Liking ratings of both the therapist and the senior advisor were largely unrelated to treatment success (p-values > .15; partial ηs2 < 0.0270). None of the four predictor*group interactions were significant. Conclusions: Firstly, therapists may have a good sense of whether the symptoms of their patient will improve after only four therapy sessions. Further research should clarify whether early clinical assessment by therapists is a substantive source of information that can be expanded upon and integrated into individualized treatment, or whether it acts as a self-fulfilling prophecy. Secondly, the lack of substantial association between therapist’s low liking of their patients is encouraging, given that ratings ranged from as low as 4/10 to 10/10, yet outcomes remained stable within these structured and supervised PTSD protocols. Further research should clarify whether this advantage also applies to treatments with a low degree of manualization and supervision. Trial registration: German Clinical Trials Register identifier: DRKS00005578.. Therapists accurately predicted PTSD symptom improvement after only four therapy sessions, suggesting that clinical intuition provides valuable early treatment information.This finding suggests that therapist intuition deserves further investigation as a potentially useful tool for early treatment planning.Personal liking of patients by therapists was not related to treatment outcomes, supporting the robustness of structured PTSD therapies regardless of personal affinity. Therapists accurately predicted PTSD symptom improvement after only four therapy sessions, suggesting that clinical intuition provides valuable early treatment information. This finding suggests that therapist intuition deserves further investigation as a potentially useful tool for early treatment planning. Personal liking of patients by therapists was not related to treatment outcomes, supporting the robustness of structured PTSD therapies regardless of personal affinity.
Gesehen am 01.12.2025